Changes of Structural Properties in Polycrystalline Y2O3 during Heating in Air and Vacuum - Solovyeva, A. E. (Refractories and industrial ceramics, 2024)
Polymorphic transformations of the first and second kind of the type C ordered cubic structure into the type C 1 disordered structure were found during heating of samples of Y 2 O 3 oxide grade (99.990%) for phosphors in the range 500 – 1100°C in air and vacuum. The phase transformations proceeded without changing the chemical composition of oxygen in yttrium oxide. The mechanism of these transformations was determined. The chemical composition of oxygen in cubic C 1 Y 2 O 3 was stable up to 1750°C in air and up to 1500°C in vacuum. The change in the chemical composition of Y 2 O 3– x with respect to the oxygen content in the C 1 type cubic phase was studied. This structure was stable up to 2200°C in air and up to 1800°C in vacuum. The disordered type C 1 phase decomposed at these temperatures into the ordered type C x phase and a monoclinic type B phase. It was theoretically substantiated and experimentally confirmed for the first time that when samples were heated in the range 2100 – 2200°C in vacuum and the oxygen stoichiometry deviated to the composition YO 1.37 , the type C x cubic phase decomposed into two cubic phases: type F with anionic vacancies and lattice parameter a = 0.5265 nm (space group Fm 3 m ) and type C 11 cubic phase with color centers and lattice parameter a = 1.0652 nm (space of group Ia 3). The refractive indices of these phases were determined. The type F and C 11 phases were stable when heated in air to 1300°C. The yttrium oxide samples were oxidized in air in the range 1300 – 1400°C to the composition Y 2 O 3 . The energy of oxygen migration into the yttrium oxide lattice was determined. The diffusion rate of oxygen during oxidation was calculated. The diffusion rate was found to depend on the temperature of oxidation and holding.